Anatomical Structure of Caudal Venae Cavae and its Anastomosis with Hepatic Veins in the Buffalo (Buballus Bubalis) - Karimi, Hamid; Ardalani, Ghaffar; Mozzaffari, Alireza (Journal of Buffalo Science, 2019)
The liver is the largest gland in the digestive system. Most parts of the liver are placing in the right region of the abdominal cavity and fixed by special ligaments, arteries and veins. The blood of the digestive system is drained into the liver by the portal vein. In this survey, the relationship between portal vein with hepatic veins, types of hepatic veins, manner of drainage of hepatic veins and also manner of drainage of the portal vein into caudal vena cava are studied. Thirty healthy livers of buffalo are selected from Urmia industrial slaughterhouse and biometrical studies performed on them. Also, the latex injection is used for observation of anastomosis of different veins in the liver. Results of liver biometry are followed: Average of weight of liver = 4380±1173/30gr, average of length of liver = 467.5±47/00972mm, average of wide of liver = 270.8±38/90934 mm270.8±38/90934 mm, average length of gallbladder = 109.66±13/7673mm, average of wide of gallbladder = 70.4±17/7426mm, average of caudal vena cava canal = 151.06 ±28.6854, Average of diameter of portal vein = 30.93±4.4430 and average of caliber of portal vein in entrance to liver = 39.26±6.2098. The liver veins were short veins, which are occupied parenchyma of the liver. These veins are received more branch of small veins. All of these veins were draining into abdominolateral wall of inter hepatic part of the portal vein. Results of this research are showed which inter hepatic veins have a different diameter. Rang of this diameter was from 0.5 to 3 mm or more. Interhepatic veins were classified according to the size of their calibre into three groups, large intrahepatic veins (they were generally more 3mm in diameter), intermediate interhepatic veins (they were 1to 3 mm in diameter) and small interhepatic veins (they were less 0.5 to 1 mm in diameter). Results of this study are showed which the average number of large foramen were 3.8, the average number of medium foramen was 8.3, and an average number of small foramen was 36.56. The studies on derivatives of portal vein on the buffalo liver have appeared which portal veins are dividing three principals trunks (left, middle and right). Left principle trunk is dividing into three branches (proximal, middle and distal). The outlet of all three types of hepatic veins had a valvular fold in entrance into caudal vena cava, which is named operculum the direction of this valve was toward the heart. Also, these research results have appeared which liver of buffalo is weightier and bigger than cattle.